Is Morality Policy Different? Testing Sectoral and Institutional Explanations of Policy Change. - Hurka, Steffen; Adam, Christian; Knill, Christoph (Policy Studies Journal, 2017)
We analyze morality policy change from the perspective of punctuated equilibrium theory (PET) to test whether reform dynamics in this policy sector follow a distinct pattern. First, we propose a new measurement scheme capturing changes in the intensity of morality policy output. Second, we demonstrate that morality policy change is strongly punctuated. Finally, and most importantly, we show that the degree of policy punctuations varies between different domains of morality policy, but not according to institutional features operating on the country level, supporting existing PET research, which has discovered similar domain-specific dynamics in changes of public spending. Specifically, punctuations are particularly pronounced in areas of manifest morality policy, that is, policies characterized by strong value conflicts, whereas punctuations are less pronounced for latent morality policies, that is, policies in which other dimensions of conflict are present next to the value dimension. Significant differences in reform dynamics are neither discerned for countries belonging to the religious or the secular world, nor for countries with majoritarian or consensual democracies. The analysis relies on an original dataset capturing legislative changes in five manifest (abortion, euthanasia, prostitution, pornography, and homosexuality), and three latent morality policies (drugs, gambling, and handguns) in 19 European countries (1960-2010).